Structural and dynamic functions establish chromatin domains. - Ishii, K.; Laemmli, U.K. (Molecular Cell, 2003)
Drosophila and mammalian proteins protect genes from heterochromatic repression in Saccharomyces cerevisiae by two different mechanisms. Factors termed genuine boundary activities (BAs) establish a structural, unidirectional bulwark against heterochromatin. In contrast, factors termed desilencing activities (DAs) act by the formation of a bidirectional, euchromatic island that blocks spreading of heterochromatin. The Drosophila boundary protein BEAF and, unexpectedly, the mammalian factor Sp1 exhibited a robust BA in yeast. In contrast, mammalian CTCF, Drosophila GAGA factor, yeast Gcn5p, and many mammalian transcription factors, although inactive as upregulators of nonsilenced genes, work as DAs. DAs but not BAs protect telomere-linked genes from silencing, presumably due to looping of telomeres and ensuing multidirectional silencing. The data demonstrate that "genetic autonomy" of chromatin domains is established by both passive and active mechanisms.